The Effects of Sex, Marital Status, and Educational Background on Selection Decisions - Renwick, Patricia A.; Tosi, Henry L. (Academy of Management Journal, 1978)
Graduate students in administration (n = 80) rated bogus resumes on applicant suitability for two managerial positions in a simulation of the conditions typically encountered by decision makers in selection situations. An analysis of variance indicated that both undergraduate major and graduate degree influenced ratings of suitability. Significant interactions were observed for job type and graduate degree and for job type and marital status. Finally, a significant interaction for sex, marital status, undergraduate major and graduate degree suggested that certain configurations of applicant characteristics were perceived as more suitable than others.